A Survey of Consensus Algorithms for Blockchain Technology - Alsunaidi, Shikah J.; Alhaidari, Fahd A. (2019 International Conference on Computer and Information Sciences (ICCIS), 2019)
Blockchain technology is a new shift in the Internet world, it has brought about changes in many sectors. Where transactions can be securely accomplished via point-to-point connections in a distributed system without the need for a third-party, with the help of consensus algorithms. In this paper, we will conduct a comprehensive survey on the Blockchain technology with focusing in the popular consensus algorithms, in order to figure out their features, and the factors that affect the performance and security. Also, we will provide a classification of the consensus algorithms and we will perform a comprehensive comparison of studied consensus algorithms. In addition, we will provide a detailed discussion of the consensus algorithms that studied with an analysis of the main factors affecting these algorithms. Finally, we will refer to some recommendations that must be considered and which can contribute to the development of this area.